The Role of Social Capital and the Implementation of Mudharabah Contracts in MSMEs in Padang City, West Sumatra - Falka Trijata, Putri Aglaia; Girindra Mega Paksi (Islamic Economics and finance in Focus, 2025)
One concept originating from the Islamic faith, which is the most widely practiced religion in Indonesian society, is the concept of Sharia. The Sharia concept refers to a set of rules and principles derived from Islamic teachings that serve as guidelines for the lives of Muslim communities. The aim of this research is to investigate the Role of Social Capital and the Application of Mudharabah Contracts in Ikaboga Micro, Small, and Medium Enterprises (MSMEs) under the Subana Bana Randang Brand in the city of Padang, West Sumatra. The research methodology employed is qualitative research. Primary data is utilized in this study. Data collection techniques include documentation, observation, and interviews. Data analysis techniques involve qualitative data analysis, comprising data reduction, data presentation, and drawing conclusions.